Climate change perception and adaptation strategies of rice seed growers in Chitwan district, Nepal - Rabin Thapa; Shiva Chandra Dhakal (Farming System)
The rice seed sub-sector plays a vital role in the self-sufficiency of rice grain and food security in the context of changing climate. Thus, it is imperative to understand the perception of rice seed growers towards climate change and identify the major adaptation strategies against climate change along with their significant determinants. In this light, our study used data from 223 rice seed growers in the Chitwan district of Nepal using purposive sampling followed by simple random sampling from Bharatpur Metropolitan City and Madi Municipality. Descriptive statistics were used to illustrate perception and adaptation strategies. The growers were categorized as adopters or non-adopters of strategies using the adoption index. Probit regression was used to determine the significant determinants of the adoption of strategies. The findings revealed that 71% of growers perceived climate change: increased temperature and decreased frequency of rainfall. Varietal selection, green manuring, planting time, improved water management and nutrient management were the major adaptation strategies adopted in the study area. From the regression analysis, years of formal education, experience, contact with extension agents and training were found to be significant determinants of the adoption of strategies. The farmers of Madi were found to be more likely to adopt the adaptation strategies. It is therefore recommended that the local and provincial-level governments explore the institutional service provision system and socio-economic characteristics while considering the location for better farm-level adoption of strategies. The study is useful for policymakers to deliberately target formal education, extension services and training for increased adoption of adaptation strategies in the face of climate change. The identified adaptation strategies and their significant determinants are applicable for the rice seed farming system in similar agro-ecological regions globally.